Impact of Digital Media on Science Learning at Upper Primary Level in Government Schools - Somasundharam, D. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Towards Effective Science Learning, a lot of emerging technologies like Information and Communication Technology (ICT) @ Schools, Smart cum Interactive Boards, Mobile Apps, etc., are playing a vital role. Scientific concepts are now easy to interpret among children to understand & response. So here I can use New and Emerging Digital Media as a tool for effective learning of Science at Upper Primary Level. Most often we handled the class using TLM, doing some experiments from Science Kits, field trips, etc., In this project, effective usage of New Digital Media like Smart cum Interactive Board, DIKSHA App, etc are taken as a tool for Pedagogy to learn Scientific concepts easily & quickly with complete understanding.